Coastal Vulnerability Index Mapping Using Remote Sensing and GIS Techniques: A Comparative Study of Oaxaca (Mexico) and Bali (Indonesia) - Aisyah, Siti; Tambunan, Mangapul Parlindungan (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
This study aims to conduct a comparative analysis of two journal articles that assess coastal vulnerability using the Coastal Vulnerability Index (CVI), focusing on the State of Oaxaca in Mexico and the Province of Bali in Indonesia. The comparison covers the research context, data inputs, methodological frameworks, findings, and conclusions, while also highlighting the respective strengths and limitations of each study. Both regions applied CVI methodologies to evaluate areas at risk from sea-level rise, utilizing remote sensing data and Geographic Information System (GIS) tools at a regional scale. The outcomes of this research emphasize key parameters that significantly affect coastal vulnerability. These insights can contribute to raising awareness among policymakers and stakeholders, supporting the formulation of effective mitigation and adaptation strategies. Moreover, the findings may serve as a foundational reference for planning and implementing sustainable coastal management initiative